2017
DOI: 10.4309/jgi.v0i36.3978
|View full text |Cite
|
Sign up to set email alerts
|

What is the harm? Applying a public health methodology to measure the impact of gambling problems and harm on quality of life.

Abstract: While the PGSI is indeed an established index of problem-gambling symptoms, it nevertheless does not quantify the degree of harm experienced by individuals at different points on the spectrum of gambling problems. The purpose of the present study was to establish the relationship between the PGSI category and health-related quality of life (HRQoL) decrements using a population health (PH) method. Harms reported by gamblers and affected others across the PGSI spectrums were transformed into 798 vignettes. A gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
99
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(125 citation statements)
references
References 15 publications
3
99
0
Order By: Relevance
“…In contrast, the PH approach emphasizes the distinction between risk factors – such as excessive gambling or psychological dependence and the sequelae – the negative consequences of such behaviors or conditions. Furthermore, the PH perspective encourages thinking about both gambling and negative consequences on a continuum, ranging from low/negligible to intense/severe, with progressively decreasing population prevalence toward the more severe end of the spectrum ( Browne, Rawat, et al., 2017 ; Li, Browne, Rawat, Langham, & Rockloff, 2016 ; Shaffer & Korn, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, the PH approach emphasizes the distinction between risk factors – such as excessive gambling or psychological dependence and the sequelae – the negative consequences of such behaviors or conditions. Furthermore, the PH perspective encourages thinking about both gambling and negative consequences on a continuum, ranging from low/negligible to intense/severe, with progressively decreasing population prevalence toward the more severe end of the spectrum ( Browne, Rawat, et al., 2017 ; Li, Browne, Rawat, Langham, & Rockloff, 2016 ; Shaffer & Korn, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Browne, Rawat, et al. ( 2017 ) applied PH elicitation protocols to estimate the typical decrement to quality of life associated with each PGSI risk category. Adjusting for population prevalence, they found that at the population level, most harm (treated as a total decrement to quality of life) was attributable to lower risk categories.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While academic research has traditionally focused on the harms associated with problem or pathological levels of gambling, research now suggests that gambling harm may also occur for those with low or moderate levels of gambling, with the burdens associated with gambling harms now comparable with those associated with alcohol misuse and major depression [3]. Each year, approximately 400,000 Australian adults experience gambling-related harm or are at moderate risk of experiencing harm [4].…”
Section: Introductionmentioning
confidence: 99%